2010
DOI: 10.1038/hr.2010.172
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension in pregnant women: a population-based case–control study of pregnancy complications and birth outcomes

Abstract: Hypotension is frequent in pregnant women; nevertheless, its association with pregnancy complications and birth outcomes has not been investigated. Thus, the aim of this study was to analyze the possible association of hypotension in pregnant women with pregnancy complications and with the risk for preterm birth, low birthweight and different congenital abnormalities (CAs) in the children of these mothers in the population-based data set of the Hungarian Case-Control Surveillance of CAs, 1980CAs, -1996 Prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Shoji et al found that the lowest intradialytic systolic BP was a significant risk factor for higher mortality and that intradialytic diastolic BP,59 mmHg was associated with a significantly higher risk of death from CV and cerebrovascular disease (7). This effect has also been seen in patients who experience perioperative hypotension (18,19) and peripartum hypotension (20). However, given the alarmingly high prevalence of hypotensive events and the poor underlying CV substrate for many dialysis patients, the relationship between hypotension and mortality may be more important for dialysis patients.…”
Section: Discussionmentioning
confidence: 65%
“…Shoji et al found that the lowest intradialytic systolic BP was a significant risk factor for higher mortality and that intradialytic diastolic BP,59 mmHg was associated with a significantly higher risk of death from CV and cerebrovascular disease (7). This effect has also been seen in patients who experience perioperative hypotension (18,19) and peripartum hypotension (20). However, given the alarmingly high prevalence of hypotensive events and the poor underlying CV substrate for many dialysis patients, the relationship between hypotension and mortality may be more important for dialysis patients.…”
Section: Discussionmentioning
confidence: 65%
“…Combined with the lowering of maternal blood pressure that naturally occurs at the beginning of pregnancy, unintentional hypotension may play a role in impairing fetal development. However, this theory is not supported by limited available evidence (Banhidy, Acs, Puho, & Czeizel, ).…”
Section: Discussionmentioning
confidence: 93%
“…Two other studies ( Magee et al, 2003 ; Baggio et al, 2011 ) reported that hydralazine could lower blood pressure more than labetalol, leading to a higher incidence of maternal hypotension. However, lowering blood pressure was not advisable because hypotension can impair uteroplacental circulation and increase the risk of severe nausea, vomiting, threatened abortion, and anemia ( Bánhidy et al, 2011 ; Baggio et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%